If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x-2)-7x=-23
We move all terms to the left:
4(x-2)-7x-(-23)=0
We add all the numbers together, and all the variables
-7x+4(x-2)+23=0
We multiply parentheses
-7x+4x-8+23=0
We add all the numbers together, and all the variables
-3x+15=0
We move all terms containing x to the left, all other terms to the right
-3x=-15
x=-15/-3
x=+5
| 4u-17=59 | | 5(w-6)-8w=-21 | | -10f-10=-6f+10 | | 6=-5t+4t | | -5y+3(y+2)=10 | | -4=b-7 | | 8b+4b=-60 | | 3(2x-3)+x=4(x+2) | | 3(-1)-2y=32 | | 14(4r-8)=r-2 | | -7c+6=-8c | | -9+w/3=-4 | | -5f=-45= | | 9/7-5/2u=-4/3 | | -4=-11+b/3 | | -4g^2+6=-10 | | 13t-7=36 | | 3p=8+2p | | y-2(3y+1)=4(y-1) | | .75=3p+5.88 | | 8m+m=9 | | 3/4n=9/6 | | -2y+3+7y=-12 | | 4u+9u=0 | | 4(v-3))-6v=-2(v+6) | | 6r=-9+5r | | 1/4y-6=-10 | | 8-7c=36 | | 7x+10+10x-14=13 | | d-2=-7= | | 8–7c=36 | | -3z-8z=33 |